2012
DOI: 10.1128/aac.05363-11
|View full text |Cite
|
Sign up to set email alerts
|

Global Analysis of the Staphylococcus aureus Response to Mupirocin

Abstract: In the present study, we analyzed the response of S. aureus to mupirocin, the drug of choice for nasal decolonization. Mupirocin selectively inhibits the bacterial isoleucyl-tRNA synthetase (IleRS), leading to the accumulation of uncharged isoleucyl-tRNA and eventually the synthesis of (p)ppGpp. The alarmone (p)ppGpp induces the stringent response, an important global transcriptional and translational control mechanism that allows bacteria to adapt to nutritional deprivation. To identify proteins with an alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
53
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(60 citation statements)
references
References 122 publications
(121 reference statements)
7
53
0
Order By: Relevance
“…However, one can assume that under more physiological conditions, the impact of the enzymes may differ substantially. This is supported by the observation that the cell wall stress stimulon (27,28) has little overlap with the stringent response imposed by amino acid limitation or mupirocin (23,44,45). Thus, whether there is a quantitative or qualitative difference between the outcomes of RSH versus RelP/Q activity in S. aureus needs further evaluation.…”
Section: Discussionmentioning
confidence: 71%
“…However, one can assume that under more physiological conditions, the impact of the enzymes may differ substantially. This is supported by the observation that the cell wall stress stimulon (27,28) has little overlap with the stringent response imposed by amino acid limitation or mupirocin (23,44,45). Thus, whether there is a quantitative or qualitative difference between the outcomes of RSH versus RelP/Q activity in S. aureus needs further evaluation.…”
Section: Discussionmentioning
confidence: 71%
“…In contrast, the expression of the enterotoxin gene set7 decreased with OHM in LAC but not LAC⌬agr, and OHM had no effect on the expression of the saeR component of the SaeRS virulence regulator. Likewise, the transcription of genes involved in the stress response (asp23, crtM, and clpB) was not altered by OHM, suggesting that OHM does not induce a general stress response in LAC under the conditions tested (50)(51)(52)(53)(54). Among the metabolism genes examined, OHM had no significant effect on the transcription of the genes involved in electron transport (atpG and sdhA).…”
Section: Resultsmentioning
confidence: 89%
“…The Society of Thoracic Surgeons practice guidelines upon antimicrobial prophylaxis recommend routine 5-d mupirocin 2% nasal administration for all patients undergoing cardiac surgery in the absence of a documented negative testing for staphylococcal colonization [41] . However, concerns still remain about the extensive use of mupirocin because of lack of efficacy, risk of widespread high-level resistance, and costs [42][43][44] . A systematic review of the literature and meta-analysis by Kallen et al [45] demonstrated a 45% reduction in surgical site infections (SSIs) caused by Staphylococcus aureus with the use of preoperative mupirocin among cardiac surgery patients known to be colonized with Staphylococcus aureus.…”
Section: Risk Factorsmentioning
confidence: 99%